Proteinase-activated receptor 2 promotes 3T3-L1 preadipocyte differentiation through activation of the PI3K/AKT signalling pathway and MAT2A gene expression. (19th October 2020) - Wang, Xiaojuan; Liang, Fang; Fan, Hui; Wang, Zhijie; Gou, Xiaolin; Ning, Yu
Abstract: The present study aimed to investigate the function and mechanisms of PAR2 in preadipocyte differentiation. This study found that the expression level of PAR2 was increased during 3T3-L1 mouse preadipocyte differentiation towards adipocytes. In addition, PAR2 overexpression significantly stimulated the expression of adipogenic proteins including ACC1, PPARγ, and SREBF1. Moreover, PAR2 overexpression increased the content of triglyceride (TG) in 3T3-L1 preadipocytes. Knockdown of PAR2 suppressed 3T3-L1 preadipocyte differentiation and adipogenesis. Mechanistically, PAR2 promoted 3T3-L1 preadipocyte differentiation and TG production through activation of the PI3K/AKT signalling pathway and MAT2A gene expression. The research sheds light on the adipogenic effects of PAR2 and its underlying mechanisms. Thus, PAR2 may have therapeutic significance for obesity.